PENGELOLAAN HUTAN KEMASYARAKATAN DILIHAT DARI PERSPEKTIF ISLAM DI KAWASAN HUTAN SESAOT KABUPATEN LOMBOK BARAT. - Moh. Huzaini; Akhmad Jufri; Dema Arkandia (Jurnal Ilmiah Ekonomi Islam, 2023)
Abstract The aim of this studi was to analyze the ways and reasons for community forest managers utilizing forest resources from the perspective of Islamic economics and conservation as well as their welfare. The type of study is descriptive, the research approach is qualitative. This study was conducted in the Sesaot forest area of West Lombok Regency. The data collection techniques were observation and in-depth interviews. Determination of informants using purposive and snoball techniques. The stages of data analysis include reduction, data display and drawing conclusions. From a study on the utilization of forest resources, most of the farmers managing the Sesaot community forest have utilized forest resources in accordance with Islamic economic and conservation principles (al-intifa’, al-i’tibar and al-ishlah). Such farmer behavior is driven by the understanding the work is worship, by always looking after and caring for their plants to get maximum results. From a welfare study, most of the farming families are already prosperous, because they are able to meet their dharuriyyat and hajiyyat needs.Farmer families have also earned a good life (hayyatan tayyibah) as mentioned in the qur’an an-Nahl (16 : 97) and the are qana’ah even though the live insimplicity.